The Dialectic of at-Turath Wa At-Tajdid : a Critique of Hasan Hanafi's Islamic Left - Wahyudi Nurman (Pascasarjana UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
Islamic Left is an idea in a large project called at-Turats wa at-Tajid which Hasan Hanafi has been working on since attending lectures at Sorbone University, France. Islamic Left is projected as an idea to realize a social revolution in the order of Islamic society so that it can get out of colonialism and poverty. and being left behind and being able to fight against Western hegemony over the Eastern world. The Islamic Left itself is a big project that can be realized through three main steps, namely, by renewing the treasures of classical Islamic scholarship, opposition to Western civilization and national unity from various Islamic backgrounds, thought and religion. As a product of thought that has spread to the public sphere, the Islamic Leftist view initiated by Hasan Hanafi has received a lot of criticism from various Islamic figures, especially regarding his efforts to renew classical Islamic treasures. This article aims to reveal and analyze certain themes in the renewal of classical Islamic treasures promoted by Hasan Hanafi as the first step to realizing the Islamic Left as well as describing several criticisms of his thinking. This research uses descriptive methods to describe these concepts by conducting library research to obtain the sources. Kiri Islam merupakan sebuah gagasan dalam proyek besar bernama at-Turats wa at-Tajid yang digarap oleh Hasan Hanafi semenjak mengikuti perkuliahan di Univeritas Sorbone, Perancis.Kiri Islam diproyeksikan sebagai gagasan untuk mewujudkan revolusi social dalam tatanan masyarakat Islam sehingga bisa keluar dari penjajahan,kemiskinan dan ketertinggalan serta mampu melawan hegemoni Barat terhadap dunia Timur.Kiri Islam itu sendiri merupakan proyek besar yang dapat diwujudkan melalui tiga langkah utama yaitu, dengan melakukan pembaharuan khazanah keilmuan Islam klasik,penentangan terhadap peradaban Barat dan persatuan kebangsaan dari berbagai latar belakang aliran islam,pemikiran dan agama.Sebagai sebuah produk pemikiran yang telah tersebar keranah public,pandangan Kiri Islam yang dicetuskan oleh Hasan Hanafi telah banyak mendapat kritikan dari berbagai tokoh Islam terutama terkait usaha pembaharuan khazanah Islam klasik yang dilakukannya.Artikel ini bertujuan untuk menyingkap dan menganalisa tema-tema tertentu dalam pembaharuan khazanah Islam klasik yang diusung oleh Hasan Hanafi sebagai langkah awal untuk mewujudkan Kiri Islam serta menggambarkan beberapa kritikan terhadap pemikirannya tersebut.Penelitian ini menggunakan metode deskriptif untuk menggambarkan konsep-konsep tersebut dengan melakukan penelitian kepustakaan untuk mendapatkan sumber-sumbernya.